Simulation of optical interconnects for future computing systems - Tjew, Adan Yu Song (2014)
Nanometer-length play an important role on incoming and outgoing for future challenge in communication technology. The simulation of light excitation propagates along Au(gold) nanoparticles chains waveguide were carried out by the software called COMSOL. The effect of Au LSPPs(localized surface plasmnon polariton) can be simulate by more realistic experimentally in the gold dielectric function.